Chinese college sports programs and cultural construction with the United States sport education mode - Zhu, W. (International Journal of Sports Science and Engineering, 2008)
The Ministry of Education in 2002, "National College of Physical Education Curriculum Teaching Instruction" after the enactment of the National College of Physical Education set off an upsurge in cultural construction, the college physical education modernization has been to deepen the study, sports and physical function Development functions have been unprecedented attention. However, advanced the idea of a certain system of colleges and universities can not guarantee that physical education and cultural construction with the times and the smooth progress of modernization, advanced and practical curriculum and teaching model is the idea of courses and programs to ensure the implementation of the specific culture. Learning and the introduction of international advanced curriculum and teaching model on China's college sports culture courses will play a more effective role. Education campaign in the United States and the United States as a model of the most famous one of the curriculum and teaching model, currently the world have been and learn from a wide range of applications, colleges and universities in China to study its physical education curriculum and teaching model of the design will be a good reference, China's colleges and universities in order to achieve the physical education culture.